Metronomic chemotherapy offsets HIFα induction upon maximum‐tolerated dose in metastatic cancers - Luana Schito; Sergio Rey; Ping Xu; Shan Man; William Cruz‐Muñoz; Robert S Kerbel (EMBO Molecular Medicine, 2020)
Abstract Conventional maximum‐tolerated dose (MTD) chemotherapy relies on periodic, massive cancer cell ablation events followed by treatment‐free intermissions, stereotypically resulting in resistance, relapse, and mortality. Furthermore, MTD chemotherapy can promote metastatic dissemination via activation of a transcriptional program dependent on hypoxia‐inducible factor (HIF)‐1α and (HIF)‐2α (hereafter referred to as HIFα). Instead, frequent low‐dose metronomic (LDM) chemotherapy displays less adverse effects while preserving significant pre‐clinical anticancer activity. Consequently, we hereby compared the effect of MTD or LDM chemotherapy upon HIFα in models of advanced, metastatic colon and breast cancer. Our results revealed that LDM chemotherapy could offset paralog‐specific, MTD‐dependent HIFα induction in colon cancers disseminating to the liver and lungs, while limiting HIFα and hypoxia in breast cancer lung metastases. Moreover, we assessed the translational significance of HIFα activity in colorectal and breast TCGA/microarray data, by developing two compact, 11‐gene transcriptomic signatures allowing the stratification/identification of patients likely to benefit from LDM and/or HIFα‐targeting therapies. Altogether, these results suggest LDM chemotherapy as a potential maintenance strategy to stave off HIFα induction within the intra‐metastatic tumor microenvironment.